Participatory Research With an Online Drug Forum: A Survey of User Characteristics, Information Sharing, and Harm Reduction Views - Chiauzzi, E.; DasMahapatra, P.; Lobo, K.; Barratt, Monica (Informa Healthcare, 2013)
Visitors to a popular online drug forum completed an online survey between November 2011 and January2012, which covered (1) demographic characteristics,(2) substance use (including nonmedical prescription opioid use), (3) forum activity, and (4) harm reduction beliefs. The study sample (N = 897) primarily included Caucasian males in their twenties from the United States, the United Kingdom, Australia, and Canada. The practice of harm reduction was overwhelmingly endorsed by participants. Current nonmedical prescription opioid users reported more activity in forums and past substance abuse treatment. The study’s implications and limitations are noted and future research is suggested.